(3GdETGQI Edi SjQI GdeUWai hJGQjN ef HYOg ef GdNdaGAs - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s
(3ChdgG (B:s
(3HYO MeO Gddg GdbgGQ abO fOH CaVd GdYLe hGdYQH Edi JdNjU SjQI GdoeUWai abUOJ GdESJNGQI hdNUJ eYXe gPg GdETGQI s
(3BNQgG (B:s
(3hCQi GdfYje hcd eGjdgi Hg jhekG jUjQ Edi Hdi hfaGO s
(3GfXQ GdbSe GdKGfj HQbe (B580 (3hGdbSe GdKGdK HQbe (B889s
(3aj BNQgG bQGDGJs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs